The Impact and Implication of Peripheral Vascular Leakage on Ultra-Widefield Fluorescein Angiography in Uveitis - Thomas, Akshay S. (Ocul Immunol Inflamm, 2017)
PURPOSE: To study if peripheral vascular leakage (PVL) on ultra-widefield fluorescein angiography (UWFFA) prognosticates complications of uveitis or necessitates treatment augmentation. METHODS: Retrospective cohort study of uveitis patients imaged with UWFFA and ≥1 year of follow-up. RESULTS: We included 73 eyes of 42 patients with uveitis. There was no difference in baseline, intermediate, final VA (p=0.47–0.95) or rates of cystoid macular edema (CME) (p=0.37–0.87) in eyes with PVL vs. those without. Eyes with PVL receiving baseline treatment augmentation were more likely to have baseline CME but were not more likely to have impaired visual acuity at final follow-up. PVL was independently associated with treatment augmentation on generalized estimating equation analysis with multivariable linear regression (OR: 4.39, p=0.015). CONCLUSIONS: PVL did not confer an increased risk of impaired VA or CME at ≥1 year follow up but was possibly an independent driver of treatment augmentation.